EXTERNAL POST-MORTEM APPEARANCE INCLUDING INVOLUNTRY DISCHARGE WITH ASSOCIATED TRAUMA IN HANGING AND LIGATURE STRANGULATION IN AJMER DISTRICT OF RAJASTHAN (Journal of Forensic Medicine & Toxicology, 2022)
Hanging has been observed as one of the oldest and widely used human execution method worldwide and is also a standard lawful method well known as Judicial Hanging. of ligature strangulation it was reddish brown and in two (2) cases parchmentisation was observed. Man has adopted various methods of suicide from hanging,slaying by sword as in the biblical times or intoxication,poisoning, self immolation, and in modern days jumpingagainst a moving train, jumping from high rise building,use of fire arms.Hanging has been observed as one of theoldest and widely used human execution method worldwideand is also a standard lawful method well known as Judicial Hanging. Hanging and strangulation differs from eachother, there is neck constriction irrespective of the effectof body weight (Keithmant)1The injury to the neck orcompression of the neck involving the important structures may prove fatal. Hanging may be of different type i.e.,homicidal, judicial or autoerotic (Camps et al)2 Hanging isone of the most common methods of suicide in India also.
Keywords: Associated trauma; External Appearance; Hanging; Ligature Strangulation; Ligature Mark; Involuntary discharge; Post-mortem Interval